Are We (and Can We Be) Genuinely Inclusive? Hos[ti]pitality in Occupational Therapy Education, Practice, and Research. - Taff, Steven D.; Babulal, Ganesh M.; Hamed, Razan (American Journal of Occupational Therapy)
Inclusion and belonging are fundamental human needs and key to the engagement and well-being of occupational therapy practitioners, scientists, educators, and learners. Despite this, the profession has struggled throughout its history to act on its values as focused on wide-ranging perspectives of occupational engagement in diverse cultural contexts. Issues of diversity, equity, inclusion, justice, and accessibility (DEIJA) innervate contemporary discourse, but there is a real danger that these conversations remain at a superficial level and stop short of attempts at genuine disruption of the deeply rooted colonial systems that exist in the profession. In this column, we use Jacques Derrida's concept of hos[ti]pitality to problematize DEIJA initiatives by asking whether occupational therapy can be genuinely inclusive or if minoritized persons will always be "guests" who are expected to reciprocate their presence. We then extend this theoretical approach to inform practical ideas to disrupt hos[ti]pitality in education, practice, and research, promoting antiracist and inclusive educational settings and deconstructing barriers to more authentic inclusion of marginalized identities. Although occupational therapy cannot be fully and unconditionally hospitable, we suggest that generative disruption at both the micro and macro levels can lead to a sense of solidarity that benefits the profession and the people and communities we serve. In this column, the authors use Jacques Derrida's concept of "hos[ti]pitality" to problematize DEIJA initiatives by asking whether occupational therapy can be genuinely inclusive or if minoritized persons will always be "guests" who are expected to reciprocate their presence.